2003
DOI: 10.1007/s00441-003-0730-4
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of gene expression of prolactin-receptor (PRL-R) by in situ hybridization in reproductive organs of Typhlonectes compressicauda, a gymnophionan amphibian

Abstract: The expression of the long form of prolactin receptor (PRL-R) mRNAs was studied in reproductive organs from both male and female Typhlonectes compressicauda, an amphibian, by quantitative in situ hybridization. These PRL-R mRNAs were expressed in all the organs studied. In ovarian tissue, mRNAs coding for the long form of PRL-R were strongly expressed in ovaries with compact and vascularized corpora lutea, i.e., during the middle and the end of pregnancy. During the other periods of cycle, sexual rest, vitello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 44 publications
2
1
0
Order By: Relevance
“…Furthermore, PRLR was expressed in the spermatogonia and differentiating germ cells, which is consistent with previous reports [5,9,39] and could argue for some type of PRL effect on spermatogenesis. Prolactin receptor was expressed in the interstitial space in which Leydig cells are present.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, PRLR was expressed in the spermatogonia and differentiating germ cells, which is consistent with previous reports [5,9,39] and could argue for some type of PRL effect on spermatogenesis. Prolactin receptor was expressed in the interstitial space in which Leydig cells are present.…”
Section: Discussionsupporting
confidence: 91%
“…As expected, we found that PRLR was expressed in the yak kidney, liver, testicular, lung, skeletal muscle, heart and spleen and was consistent with observations reported for other species (Guillaumot et al., 1996; Lincoln et al., 2001; Pratt et al., 2015). In addition, PRLR was expressed in the Leydig cells and spermatogonia, which was consistent with the previous reports (Exbrayat & Morel, 2003; Hondo et al., 1995) and indicated that certain types of PRL affected spermatogenesis. Our results indicated that PRLR promoted spermatogenesis by effectively proliferation of Leydig cells during the development of yak testes.…”
Section: Discussionsupporting
confidence: 92%
“…In T. compressicauda, volumetric variations and number of lactotropic cells vary considerably throughout the cycle. An increase of PRL-encoding mRNAs was observed from the beginning to the end of pregnancy, whereas the ratio of PRL mRNAs remain constant and low during the other periods of the cycle [43,63]. These data suggest that PRL is a crucial endocrine factor that controls the development of the genital tract during the reproductive period of both viviparous and oviparous caecilian species.…”
Section: Discussionmentioning
confidence: 87%